An Analysis of Teachers Strategy in Teaching Speaking Skills at SMP Dwijendra - Monika Rambu Boba Hua; I Gusti Ayu Indah Triana Juliari; Ni Made Dwi Utari Pusparini; Komang Satria Wirasa (LPPM Universitas Dhyana Pura, 2026)
This study aims to identify the types of strategies used by English teachers in teaching speaking skills and to analyze the most frequently used strategies at SMP Dwijendra Denpasar. This study employed a descriptive qualitative approach. The subjects of this study were three English teachers who taught Grade VII, VIII, and IX. The data were collected through classroom observations, interviews, and documentation. The results of the study showed that teachers employed various strategies in teaching speaking skills, including role play, discussion, pair work, group work, storytelling, question and answer, interview, debate, picture describing, and games-based strategies. The strategies most frequently used by all teachers were role play, discussion, question and answer, picture describing, and gamesbased strategies. Meanwhile, the interview strategy was used selectively, and the debate strategy was not used. Each teacher also tended to use one dominant strategy, where Teacher 1 used role play, Teacher 2 used pair work, and Teacher 3 used group work, depending on students’ levels and characteristics. Based on the findings, it can be concluded that selecting appropriate strategies plays an important role in improving students’ participation, confidence, and communicative competence in speaking skills. Therefore, teachers are expected to select and implement suitable strategies to support more effective speaking instruction.